Using baseball seams to alter a pitch direction: The seam shifted wake - Smith, A. W.; Smith, B. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
An experimental investigation of how seams and their orientation relative to the spin axis and flight direction can alter the formation of a wake around a baseball was conducted. Particle Image Velocimetry (PIV) was used to examine the velocity field around a baseball in specific orientations and to find the boundary layer separation location, which is the location on the baseball where the wake begins to form. Certain orientations can advance the separation point on one side of the baseball, generating a pressure force on the baseball and modifying its flight path. Using this information as a guide, baseballs were launched 55 feet (a realistic pitching distance) in orientations designed to have an asymmetric separation point. These pitches were 90 mph at spin rates near 1200RPM with a vertical spin axis perpendicular to the initial flight direction. A Rapsodo 1.0 system was used to compare the pitch locations for different seam orientations. The results of this study showed a significant and repeatable difference in the path of the baseball depending on the orientation of the seams relative to the spin axis. This effect was more significant for baseballs with larger seams.